istem Informasi Pendapatan Asli Daerah Pada Dinas Pendapatan Kabupaten Sangihe - Papuas, Alfrianus; Mustafid, Mustafid; Sarwoko, Eko Adi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Regional revenue  management requires information systems to  manage the revenue income, report  preparation and evaluation of  the effectiveness and efficiency of information technology-based revenue. This information system Debgan financial statements can be well presented, accurate, timely, and can be used directly by the user. The purpose of this research is to design and build information systems revenue (SIPAD) with the evaluation system, the applicability to the District Revenue Office Sangihe. Revenue consists of loc al taxes, fees, the company's results and the results of the other receipts or PAD. For the evaluation process , we evaluated the effectiveness and efficiency  in  order  to  measure  the  performance  of  the  management  of  PAD.  System  modeling  is  used  Unified  Modeling  Language (UML) as a standard modeling language. Information systems revenues also used to improve the per formance of local governments to manage the process of receiving PAD, and to present a report to evaluate the effectiveness and efficiency of the management of PAD. Calculation of effectiveness evaluation PAD Sangihe regency in 2011 obtained an effective criterion of 83.16 percent and an efficiency of 2.92 percent.Keywords: Information systems revenue; Revenue; Evaluation of the effectiveness and efficiency